Artificial Intelligence in Academic Environments: Reducing or Increasing Foreign Language Anxiety? - Pertiwi, Primordia Carissa; Segoh, David; Rohmadhani, Annisa (Institut Agama Islam Negeri Parepare, 2025)
The integration of Artificial Intelligence (AI) tools into language learning and teaching is rapidly advancing in academic environments. Previous research has demonstrated the potential of AI tools to enhance learners’ motivation, engagement, and attitudes while improving language skills such as speaking, writing, and reading. However, systematic reviews focusing on the role of AI technologies in managing foreign language anxiety (FLA) remain limited. This study systematically reviews the effects of AI tools on different types of FLA, including writing anxiety, reading anxiety, speaking anxiety, and general communication anxiety, in academic environments. Peer-reviewed articles were retrieved from the Scopus database and screened for relevance based on titles, abstracts, and full-text availability. Of the 59 articles identified, 11 studies published between 2022 and 2024 met the inclusion criteria. The findings reveal that AI tools, such as chatbots and automated writing evaluation systems, reduce writing and speaking anxiety by providing personalized feedback and fostering learner autonomy. However, challenges such as over-reliance on AI and limited human interaction may increase anxiety for certain learners. This review highlights gaps in the literature, emphasizing the need for longitudinal studies and hybrid learning models that combine AI technologies with teacher interventions to address learners’ cognitive and affective needs.